Reward-based crowdfunding technological projects determinants of success: A quantitative study - Khalid Mahmoud Fadlelmula Elkhidir (The Journal of Entrepreneurial Finance (JEF), 2017)
Crowdfunding success in terms of the achievement of target capital in reward-based crowdfunding projects is impacted by many factors (e.g., past created projects, campaign duration, pledged capital). This paper studies the determinants of success rate (pledged capital/target capital) or (P/T) in successful technological crowdfunding projects. The quantitative study started by data collection of 328 successful Kickstarter technological crowdfunding campaigns which are later decreased to 289 due to model censorship. Tobit model was adopted as the censored linear regression model to determine the existence of relationships between the dependent variable (P/T) and the independent variables. Results suggest that success rate is associated with 7 independent variables: visuals, duration, internal social capital, comments and education are found to impact success rate positively while target capital and past created projects are found to impact success rate negatively. The study contributes to the literature in crowdfunding by paving the path to study success factors that might impact successful technological projects, and to investigate the significance of backers' feedback and project creators' education in maximizing their campaign's outcome.
Keywords: 650; Entrepreneurial Finance; Crowdfunding Industry; Reward-based Crowdfunding; Tobit Model; Open Innovation